Pengembangan Aplikasi Monitoring Proses Penjahitan APD Berbasis Web Menggunakan Metode Extreme Programming - Hudawiguna, Sigit; Buchori, Nizar; Setiawan, Ridwan; Liyana Ulfa, Risma (Institut Teknologi Garut, 2025)
In the era of digital transformation, delays in the production process due to manual recording are still a challenge for manufacturing industry players, including PD. Arrum Berkah Sentosa which produces personal protective equipment (PPE) made from leather. This research aims to develop a web-based PPE sewing process monitoring application using the Extreme Programming (XP) method. The development process includes planning, design, coding, and testing stages. The system includes employee attendance features, recording work results, managing stock items, and weekly reporting. Testing is done through the black-box method and System Usability Scale (SUS). The test results show that the system runs according to functionality with a SUS score of 80.13, which is in the “Excellent” category. The findings show that the XP approach is effective in responding to the dynamic needs of users as well as improving production efficiency in the manufacturing MSME sector.